Composition and properties of water-soluble preparation from salmon liver - Anna I. Chepkasova; Nickolay B. Ayushin; Evgeny V. Yakush (Известия ТИНРО, 2014)
Amino acid composition and antioxidant activity are investigated for dried liver of chum salmon Oncorhynchus keta , for water-soluble preparation from the dried liver, and for 1-10 kDa fraction of the water-soluble preparation. The water-soluble preparation contains more than 60 % peptides of molecular weight 1-10 kDa, about 18 % peptides of > 10 kDa, and about 20 % low molecular peptides of molecular weight < 1 kDa. The content of combined amino acids is the highest in the water-soluble preparation (672.5 mg/g), it is lower in its 1-10 kDa fraction (544.4 mg/g) and the lowest in the dried liver (333.3 mg/g). On the contrary, the content of free ninhydrin-positive compounds is the highest in the liver (91.64 mg/g) and the lowest in the water-soluble preparation (61.36 mg/g). Relative to the level of carnosine antioxidant activity, the antioxidant activity of the dried liver is higher in 5.2 times, the activity of the water-soluble preparation is higher in 4.2 times, and the activity of the 1-10 kDa fraction is higher in 6.3 times. Three isoforms of such biologically active peptide as hepcidin are found in the 1-10 kDa fraction, their molecular weights are 2841.54, 2913.54 and 3025.63 Da.